Seroepidemiology, Diagnosis, Isolation And Characterisation Of Neospora Caninum Among Cattle In Malaysia - Cheah, Tong Soon (2004)

(untitled)
Neospora caninum is an apicomplexan protozoan parasite that has worldwide distribution and is known to cause abortion and congenital disease in cattle and dogs. This thesis deals with various aspect of investigations on neosporosis in Malaysian cattle which include seroprevalence in cattle, modes of transmission of N. caninum in cattle, effects of N. caninum infections in pregnant dairy cattle naturally infected with the parasite, isolation of N. caninum and comparison of the standard diagnostic technique, IFAT with ISCOM ELISA. A cross-sectional study was conducted in dairy and beef cattle in Peninsular Malaysia and Sabah to determine the seroprevalence of N. caninum and the association of breeds and farm location to the seroprevalence. In Peninsular Malaysia, a total of 1531sera from Sahiwal-Friesian on three large scale (D1, D2, D3) and 21 small scale (D4) farms were tested for N. caninum antibodies using the IFAT. A total of 1413 sera from beef cattle which comprised Nelore, Droughtmaster and Kedah-Kelantan on four large scale farms (B1-B4) were also tested. In Peninsular Malaysia, the seroprevalence of N. caninum in the dairy cattle ranged from 1.9% in D2 farm to 6.7% in D1 farm, while in beef animals the N. caninum seroprevalence varied between 2.0% in B4 farm and 5.4% in B2 farm. Among the dairy cattle there was significance between the seroprevalence of N. caninum in D2 farm and those of D1 and D3 farms (p<0.05). The seroprevalence of N. caninum in D1 farm was significantly higher than those in B1, B3 and B4 farms (p<0.05). The N. caninum seroprevalence in D3 farm was was significantly higher that in B4 farm. In Sabah, a total of 624 sera from Sahiwal cross and pure Friesian cattle on 6 large scale (SD1-SD6) and two small scale (SD7, SD8) farms were tested. A total of 240 sera from beef cattle which were Droughtmaster and Brahman crosses on 3 large scale (SB1-SB3) farms were tested. The seroprevalence was highest in the cattle on SD2 farm (32.5%) and lowest in the cattle on SD7 farm (2.7%). The seroprevalence of N. canium of cattle on farms SB1 and SB2 were 12.5% respectively, while in SB3 farm the figure was 2.5%.. There was a significant difference between the seroprevalence of N. caninum cattle on D2 farm and cattle on the other farms (p<0.05). In the investigation on modes of transmission, a cross-sectional study was conducted on the relationship between seropoositivity of cows and their calves after colostral intake. Blood samples were collected from 286 dams and their respective calves on D1-D3 farms and from another 233 pairs of beef cattle on B1-B4 farms. The was a strong association between seropositivity of dams and that of their calves (p<0.001).The association of seroprevalence of precolostral calves with their dams was examined by collection of blood samples from 100 dams and their calves before colostral intake. Out of the 100 dams, 13 were seropositive and produced nine (69.2%) congenitally infected calves. There was strong association between presence of antibodies in the dam and congenital infection (p<0.001). A total of 83 seronegative heifers were also monitored prospectively from birth for evidence of post-natal infection. No evidence of seroconversion was found in the seronegative heifers. A study conducted on D1 farm to assess the reproductive performance of eight pregnant seropositive heifers and 10 pregnant seropositive cows till pregnancy was terminated by abortion or parturition. Two heifers repeatedly returned to oestrus. Abortions were seen in four heifers. Two heifers produced weak and underweight calves and one of the calves died 12 hours after birth. The precolostral sera from the two calves had N. caninum antibodies. Abortion occurred in one out of the 10 pregnant cows. All the remaining nine cows produced normal calves whose precolostral and postcolostral sera were positive for Neospora antibodies. Paired serum samples from the aborted heifers and cow revealed no evidence of active infections due to Br. abortus, Leptospira spp., S. dublin, IBR virus, BVD virus or T. gondii. Reproductive disorders were commonly seen in the seropositive heifers when compared to seropositive cows and the difference was found to be significant (p<0.05).In an attempt on isolation, brain homogenate from a congenitally infected calf born to a seropositive heifer was inoculated intraperitoneally into 10 BALB/c mice. Four out of the 10 mice died during the observation period and brains from the remaining 6 were homogenised and cultured onto Vero cell lines. Tachyzoites resembled those of N. caninum were detected in the cell cultures 14 days after the inoculation of brain homogenate from one of the six mice. Serology, electron microscopy and molecular studies revealed no difference between this new Malaysian bovine isolate and reference N. caninum isolate Nc-1, confirming that it was N. caninum. The isolate was designated Nc-MalB1 A total of 661 dairy and 375 beef cattle sera from Peninsular Malaysia and Sabah were used in the comparison IFAT with ISCOM ELISA in the detection of N. caninum antibodies. Based on the cut-offs recommended by the manufacturers, there was reasonably good agreement between the two tests as indicated by high kappas’ values of 0.80 in dairy and 0.82 in beef cattle.